الصراع الداخلي على الشخصية الرئيسية في القصة القصيرة الملاك الأعرج لمنى مرشود - syarifah syarifah (Pascasarjana UIN Raden Mas Said Surakarta, 2024)
This research examines the psychological aspects in the short story